Ethical Challenges Faced by the Healthcare Workers to Provide Health Service during COVID-19 Pandemic - Shrestha, Erina; Pokharel, Rita; Mehta, Ram Sharan; Rai, Gayatri (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: Managerial, administrative, and disease-related issues during COVID-19 pressurized the healthcare workers and challenged their ethical practice. This study attempted to shed light on the ethical challenges faced by the healthcare workers during the COVID-19 pandemic at B. P. Koirala Institute of Health Sciences (BPKIHS). Methods: Descriptive cross-sectional study using convenience sampling was conducted among 108 registered doctors and nurses working in BPKIHS. Data were collected using pretested, self-designed semi-structured online questionnaires and analyzed using descriptive statistics. Results: Majority (78.7%) of the respondents feared of contracting the disease while caring for the patient. Nearly 30% respondents reported that they had to frequently work with inadequate protective measures. Fifty-four percent respondents reported that sometimes they had to continue work with suspected symptoms due to shortage of manpower. Almost half (49.1%) of the respondents had to sometimes prioritize the care among the patients due to shortage of resources. Most (72%) of the respondents never had to force COVID positive patient for hospital admission. Around 20% of the respondents had to disclose COVID status of patients without consent. Around 14% of the respondents had sometimes refused care of COVID positive patients. More than half (55.6%) of the respondents had sometimes felt that the patients did not receive holistic care. Conclusion: The major ethically challenging situations faced by healthcare workers during the COVID pandemic included continuous work with suspected symptoms due to shortage of manpower, continuing work with inadequate protective measures, and prioritizing care due to shortage of resources.